Magnetization Ground State and Reversal Modes of Magnetic Nanotori - Altbir-Drullinsky, D (American Institute of Physics, 2016)
In this work, and by means of micromagnetic simulations, we study the magnetic properties of toroidal nanomagnets. The magnetization ground state for different values of the aspect ratio between the toroidal and polar radii of the nanotorus has been obtained. Besides, we have shown that the vortex and the in-plane single domain states can appear as ground states for different ranges of the aspect ratio, while a single domain state with an out-of-plane magnetization is not observed. The hysteresis curves are also obtained, evidencing the existence of two reversal modes depending on the geometry: a vortex mode and a coherent rotation. A comparison between toroidal and cylindrical nanoparticles has been performed evidencing that nanotori can accommodate a vortex as the ground state for smaller volume than cylindrical nanorings. © 2016 Author(s).